Evaluating Therapeutic Equivalence of Generic and Original Levetiracetam in Patients with Epilepsy: A Retrospective Study - Jannapas Tharavichitkun (2022)
The brand interchangeability of antiepileptic drugs (AEDs) is a topic of debate, especially regarding their therapeutic equivalence. This study evaluates the efficacy and tolerability of generic levetiracetam compared to the brand-name equivalent in a routine clinical setting. We conducted a retrospective study, examining patients with stable seizure frequency who received generic levetiracetam after the brand-name drug. During the six-month substitution period, changes in seizure frequency, hospitalization due to seizure exacerbation, adverse events, composite outcomes related to adjusting the AED dosage, and switching back to original levetiracetam were analyzed. Seventy-five patients were enrolled; the majority (85.3%) had focal onset seizures, and almost half (49.3%) had refractory epilepsy. Six months after the substitution, the mean seizure frequency per month was not significantly different (3.15 ± 14.47 vs. 2.77 ± 11.41; p = 0.970). In patients with controlled seizures before the change, the seizure frequency increased significantly (0.56 ± 1.83 vs. 0.03 ± 0.16; p = 0.012). Adverse events occurred in six patients. We have observed recurrent seizures or adverse events from 14 days after the transition. The original drug return rates due to recurrent seizures and adverse events were 5.3% and 1.3%, respectively. Generic levetiracetam might not show therapeutic equivalence to the original molecule, especially in patients adequately controlled by the brand-name drug.